The assessment of the impact of myofascial training on postural control – a case study - Guzik, Agnieszka; Chwaszcz, Bartłomiej; Drużbicki, Mariusz; Wolan-Nieroda, Andżelina; Wyszyńska, Justyna (European Journal of Clinical and Experimental Medicine, 2017)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. A sedentary lifestyle with lack of physical activity contributes to deteriorated balance among healthy young people. Physical activity is import_ant since it stimulates neuromuscular junctions that control body posture, especially at younger age, when greater postural sway may be observed in stabilography compared to adults. Proper work of individual muscle groups is import_ant to maintain proper balance. Abnormal muscle tone can lead to dysbalances that make it difficult o maintain a stable posture in a variety of conditions. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The aim of the study was to evaluate the effect of a training cycle consisting of stretching of the ilopsoas, rectus femoris, gluteus maximus, hamstring and rectus abdominis, and eccentric training of the above mentioned muscles to improve static and dynamic balance. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Oobjective and qualitative-subjective were used to assess the results in a man aged 22 yrs. Postural control was tested twice in the patient with the Neurocom International Inc. SMART EquiTest device under static conditions without visual control and with dynamic visual surrounding and unstable support surface. Automatic postural reflexes were also evaluated. In addition, clinical tests were performed. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Myo-fascial training, which included eccentric training combined with lower limb and trunk stretching improved the postural control in the subject.